Significance of Calorie-Restricted Ketogenic Diet for Lung Cancer with Brain Metastases and Hepatoma with Pulmonary Metastases: Two Case Reports - Tan, Dong; Zhao, Jing; Yang, Wen-ru; Yuan, Fang (Archives of Clinical and Biomedical Research, 2022)
Background: Cancer cells have altered metabolism that is characterized by an enhanced uptake and utilization of glucose. These increased glucose dependence alterations, present potential vulnerabilities that could be targeted for cancer therapy. The calorie-restricted ketogenic diet (KD) may meet the requirement. Case Presentation: We present two cases of patients diagnosed with aggressive forms of cancer, lung cancer with brain metastatic tumors and primary liver cancer with pulmonary metastases. The patients began KD intervention after exhausting the other treatment options. Both of them responded to KD and demonstrated a beneficial effect. The tumor size from serial imaging and serum tumor markers were significantly reduced after KD in both subjects without any adverse effects. Both patients had tumour remission even after stopping the ketogenic diet, indicating that KD is a safe, effective treatment to aggressive cancers with metastases when used with conventional therapies. Conclusions: This study demonstrated the significant beneficial effect of a calorie-restricted ketogenic diet for two types of aggressive cancers with metastases. Even a brief KD intervention has a profound effect, implicating the significant therapeutic potential for the ketogenic diet as adjuvant therapy for cancer treatment.